QUALITY OF STEAM BROWNIES AS A FUNCTIONAL FOOD FOR PREGNANT ANEMIA IN PREGNANT WOMEN IN STUNTING PREVENTION (Journal of Pharmaceutical Negative Results, 2022)
Aim: This study aims to study and analyze the effect of beet flour substitution on manufacturing steamed brownies on the physical quality.Material and Methods: This research was conducted at the Pastry and Bakery Processing Laboratory of the Culinary Education Study Program, State University of Jakarta. The time of research starts from July 2021 to June 2022. The method used in this study is experimental. The research samples used were steamed brownies with beet flour substitution of as much as 35%, 45%, and 55%, then tested three times.Results: Based on the results of the statistical hypothesis test, the physical quality test using the ANOVA test showed that the aspects of swell ability, stability, and crumb morphology had no significant effect or difference in the substitution of beetroot flour as much as 35%, 45%, and 55% in the manufacture of steamed brownies.Conclusion: The conclusion of this study is to recommend steamed brownies with 55% beet flour substitution to be developed to optimize the utilization of beetroot flour as a nutritional value enhancer.